THE ROLE OF FAMILY IN FULFILLING ADL (ACTIVITY THE DAILY LIVING) AUTIS - Suprajitno Suprajitno; Frizcha Illah Arisky (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2018)
Children autis experienced difficulty in activity and interest that involves other human beings. The condition of children autis lets do not care yourself independently. The purpose of this research to know the role of family in fulfilling ADL (Activity the Daily Living) Autis in the centers autis Blitar City. Design this research using descriptive design. The sample in this research are a family that has an autistic child who is running or never done as many as 34 family therapy using a purposive sampling technique. Data collection used questionnaires made by the researchers. This research result indicates that the role of family in fulfilling ADL children autis in the category of 68% good (23 family), a 29% (10 family) having a level the role of enough, and 3% (1 family) have an important role less. From the kind of the indicators ADL autis, the role of family less is to achieve eat/drinking, because the autis are able to estimate the food should enter in mouth to chew and swallowed, so the family is not so supervise the child with autism eating and drinking. Recommendations of research is expected develop into therapy next on independence child in ADL that involves the family of a autis to increase a generation of kids able autis to daily activities.